Low light improves ability of Appalachian oak seedlings to compete with mesophytes in nitrogen-rich soils - Sarah L. Ottinger; Chelcy Ford Miniat; Joel Scott; Nina Wurzburger (Forest Ecology and Management, 2026)

Perspectives on the contributions of women to the hydrologic sciences and their changing demographics at USDA Forest Service Experimental Forests and Ranges - Lindsey Rustad; Mary Beth Adams; Salli F. Dymond; Margaret Gregory; Chelcy F. Miniat (Journal of Hydrology, 2023)

Nitrogen and light regulate symbiotic nitrogen fixation by a temperate forest tree - Sarah L. Ottinger; Chelcy Ford Miniat; Nina Wurzburger (Oecologia, 2023)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

The long-term case for partial-cutting over clear-cutting in the southern Appalachians USA - Katherine J. Elliott; Chelcy F. Miniat; Andrea S. Medenblik (New Forests, 2020)

Drought sensitivity of an N 2 ‐fixing tree may slow temperate deciduous forest recovery from disturbance - Jeffrey M. Minucci; Chelcy F. Miniat; Nina Wurzburger (Ecology, 2019)
Increased drought intensity and frequency due to climate change may reduce the abundance and activity of nitrogen (N 2 )‐fixing plants, which supply new N to terrestrial ecosystems. As a result, drought may indirectly reduce ecosystem productivity through its effect on the N cycle. Here, we manipulated growing season net rainfall across a series of plots in an early successional mesic deciduous forest to understand how drought affects the aboveground productivity of the N 2 ‐fixing tree Robinia pseudoacacia and three co‐occurring nonfixing tree species. We found that lower soil moisture was associated with reduced productivity of R. pseudoacacia but not of nonfixing trees. As a result, the relative biomass and density of R. pseudoacacia declined in drier soils over time. Greater aboveground biomass of R. pseudoacacia was also associated with greater total soil N, extractable inorganic N, N mineralization rates, and productivity of nonfixing trees. These soil N effects may reflect current N 2 fixation by R. pseudoacacia saplings, or the legacy effect of former trees in the same location. Our results suggest that R. pseudoacacia promotes the growth of nonfixing trees in early succession through its effect on the N cycle. However, the sensitivity of R. pseudoacacia to dry soils may reduce N 2 fixation under scenarios of increasing drought intensity and frequency, demonstrating a mechanism by which drought may indirectly diminish potential forest productivity and recovery rate from disturbance.

Shade and Hemlock Woolly Adelgid Infestation Increase Eastern Hemlock Foliar Nutrient Concentration - Marika Lapham; Chelcy Ford Miniat; Albert E Mayfield; Robert M Jetton; Steven T Brantley; David R Zietlow; Cindi Brown; James R Rhea (Forest Science, 2018)

Total C and N Pools and Fluxes Vary with Time, Soil Temperature, and Moisture Along an Elevation, Precipitation, and Vegetation Gradient in Southern Appalachian Forests - Jennifer D. Knoepp; Craig R. See; James M. Vose; Chelcy F. Miniat; James S. Clark (Ecosystems, 2018)

Cold air drainage flows subsidize montane valley ecosystem productivity - Kimberly A. Novick; A. Christopher Oishi; Chelcy Ford Miniat (Global Change Biology, 2016)
In mountainous areas, cold air drainage from high to low elevations has pronounced effects on local temperature, which is a critical driver of many ecosystem processes, including carbon uptake and storage. Here, we leverage new approaches for interpreting ecosystem carbon flux observations in complex terrain to quantify the links between macro‐climate condition, drainage flows, local microclimate, and ecosystem carbon cycling in a southern Appalachian valley. Data from multiple long‐running climate stations and multiple eddy covariance flux towers are combined with simple models for ecosystem carbon fluxes. We show that cold air drainage into the valley suppresses local temperature by several degrees at night and for several hours before and after sunset, leading to reductions in growing season respiration on the order of ~8%. As a result, we estimate that drainage flows increase growing season and annual net carbon uptake in the valley by >10% and >15%, respectively, via effects on microclimate that are not be adequately represented in regional‐ and global‐scale terrestrial ecosystem models. Analyses driven by chamber‐based estimates of soil and plant respiration reveal cold air drainage effects on ecosystem respiration are dominated by reductions to the respiration of aboveground biomass. We further show that cold air drainage proceeds more readily when cloud cover and humidity are low, resulting in the greatest enhancements to net carbon uptake in the valley under clear, cloud‐free (i.e., drought‐like) conditions. This is a counterintuitive result that is neither observed nor predicted outside of the valley, where nocturnal temperature and respiration increase during dry periods. This result should motivate efforts to explore how topographic flows may buffer eco‐physiological processes from macroscale climate change.

Declining water yield from forested mountain watersheds in response to climate change and forest mesophication - Peter V. Caldwell; Chelcy F. Miniat; Katherine J. Elliott; Wayne T. Swank; Steven T. Brantley; Stephanie H. Laseter (Global Change Biology, 2016)
Climate change and forest disturbances are threatening the ability of forested mountain watersheds to provide the clean, reliable, and abundant fresh water necessary to support aquatic ecosystems and a growing human population. Here, we used 76 years of water yield, climate, and field plot vegetation measurements in six unmanaged, reference watersheds in the southern Appalachian Mountains of North Carolina, USA to determine whether water yield has changed over time, and to examine and attribute the causal mechanisms of change. We found that annual water yield increased in some watersheds from 1938 to the mid‐1970s by as much as 55%, but this was followed by decreases up to 22% by 2013. Changes in forest evapotranspiration were consistent with, but opposite in direction to the changes in water yield, with decreases in evapotranspiration up to 31% by the mid‐1970s followed by increases up to 29% until 2013. Vegetation survey data showed commensurate reductions in forest basal area until the mid‐1970s and increases since that time accompanied by a shift in dominance from xerophytic oak and hickory species to several mesophytic species (i.e., mesophication) that use relatively more water. These changes in forest structure and species composition may have decreased water yield by as much as 18% in a given year since the mid‐1970s after accounting for climate. Our results suggest that changes in climate and forest structure and species composition in unmanaged forests brought about by disturbance and natural community dynamics over time can result in large changes in water supply.

Forest tree growth response to hydroclimate variability in the southern Appalachians - Katherine J. Elliott; Chelcy F. Miniat; Neil Pederson; Stephanie H. Laseter (Global Change Biology, 2015)
Climate change will affect tree species growth and distribution; however, under the same climatic conditions species may differ in their response according to site conditions. We evaluated the climate‐driven patterns of growth for six dominant deciduous tree species in the southern Appalachians. We categorized species into two functional groups based on their stomatal regulation and xylem architecture: isohydric, diffuse porous and anisohydric, ring porous. We hypothesized that within the same climatic regime: (i) species‐specific differences in growth will be conditional on topographically mediated soil moisture availability; (ii) in extreme drought years, functional groups will have markedly different growth responses; and (iii) multiple hydroclimate variables will have direct and indirect effects on growth for each functional group. We used standardized tree‐ring chronologies to examine growth of diffuse‐porous ( Acer , Liriodendron , and Betula ) and ring‐porous ( Quercus ) species vs. on‐site climatic data from 1935 to 2003. Quercus species growing on upslope sites had higher basal area increment ( BAI ) than Quercus species growing on mesic, cove sites; whereas, Acer and Liriodendron had lower BAI on upslope compared to cove sites. Diffuse‐porous species were more sensitive to climate than ring porous, especially during extreme drought years. Across functional groups, radial growth was more sensitive to precipitation distribution, such as small storms and dry spell length ( DSL ), rather than the total amount of precipitation. Based on structural equation modeling, diffuse‐porous species on upslope sites were the most sensitive to multiple hydroclimate variables ( r 2 = 0.46), while ring‐porous species on upslope sites were the least sensitive ( r 2 = 0.32). Spring precipitation, vapor pressure deficit, and summer storms had direct effects on summer AET / P , and summer AET / P , growing season small storms and DSL partially explained growth. Decreasing numbers of small storms and extending the days between rainfall events will result in significant growth reduction, even in regions with relatively high total annual rainfall.

Changing forest water yields in response to climate warming: results from long‐term experimental watershed sites across North America - Irena F. Creed; Adam T. Spargo; Julia A. Jones; Jim M. Buttle; Mary B. Adams; Fred D. Beall; Eric G. Booth; John L. Campbell; Dave Clow; Kelly Elder; Mark B. Green; Nancy B. Grimm; et al. (Global Change Biology, 2014)
Climate warming is projected to affect forest water yields but the effects are expected to vary. We investigated how forest type and age affect water yield resilience to climate warming. To answer this question, we examined the variability in historical water yields at long‐term experimental catchments across Canada and the United States over 5‐year cool and warm periods. Using the theoretical framework of the Budyko curve, we calculated the effects of climate warming on the annual partitioning of precipitation ( P ) into evapotranspiration ( ET ) and water yield. Deviation ( d ) was defined as a catchment's change in actual ET divided by P [ AET / P ; evaporative index ( EI )] coincident with a shift from a cool to a warm period – a positive d indicates an upward shift in EI and smaller than expected water yields, and a negative d indicates a downward shift in EI and larger than expected water yields. Elasticity was defined as the ratio of interannual variation in potential ET divided by P ( PET / P ; dryness index) to interannual variation in the EI – high elasticity indicates low d despite large range in drying index (i.e., resilient water yields), low elasticity indicates high d despite small range in drying index (i.e., nonresilient water yields). Although the data needed to fully evaluate ecosystems based on these metrics are limited, we were able to identify some characteristics of response among forest types. Alpine sites showed the greatest sensitivity to climate warming with any warming leading to increased water yields. Conifer forests included catchments with lowest elasticity and stable to larger water yields. Deciduous forests included catchments with intermediate elasticity and stable to smaller water yields. Mixed coniferous/deciduous forests included catchments with highest elasticity and stable water yields. Forest type appeared to influence the resilience of catchment water yields to climate warming, with conifer and deciduous catchments more susceptible to climate warming than the more diverse mixed forest catchments.

Divergent phenological response to hydroclimate variability in forested mountain watersheds - Taehee Hwang; Lawrence E. Band; Chelcy F. Miniat; Conghe Song; Paul V. Bolstad; James M. Vose; Jason P. Love (Global Change Biology, 2014)
Mountain watersheds are primary sources of freshwater, carbon sequestration, and other ecosystem services. There is significant interest in the effects of climate change and variability on these processes over short to long time scales. Much of the impact of hydroclimate variability in forest ecosystems is manifested in vegetation dynamics in space and time. In steep terrain, leaf phenology responds to topoclimate in complex ways, and can produce specific and measurable shifts in landscape forest patterns. The onset of spring is usually delayed at a specific rate with increasing elevation (often called H opkins' Law; Hopkins, 1918), reflecting the dominant controls of temperature on greenup timing. Contrary with greenup, leaf senescence shows inconsistent trends along elevation gradients. Here, we present mechanisms and an explanation for this variability and its significance for ecosystem patterns and services in response to climate. We use moderate‐resolution imaging spectro‐radiometer ( MODIS ) Normalized Difference Vegetation Index ( NDVI ) data to derive landscape‐induced phenological patterns over topoclimate gradients in a humid temperate broadleaf forest in southern A ppalachians. These phenological patterns are validated with different sets of field observations. Our data demonstrate that divergent behavior of leaf senescence with elevation is closely related to late growing season hydroclimate variability in temperature and water balance patterns. Specifically, a drier late growing season is associated with earlier leaf senescence at low elevation than at middle elevation. The effect of drought stress on vegetation senescence timing also leads to tighter coupling between growing season length and ecosystem water use estimated from observed precipitation and runoff generation. This study indicates increased late growing season drought may be leading to divergent ecosystem response between high and low elevation forests. Landscape‐induced phenological patterns are easily observed over wide areas and may be used as a unique diagnostic for sources of ecosystem vulnerability and sensitivity to hydroclimate change.

Drought enhances symbiotic dinitrogen fixation and competitive ability of a temperate forest tree - Nina Wurzburger; Chelcy Ford Miniat (Oecologia, 2014)